Evolution of the Earth - Stevenson, David John, 1948- (Amsterdam ; Boston : Elsevier, 2009)
This title focuses on the formation of Earth, core and continents, outgassing and volcanism, development of plate tectonics, origin and persistence of Earth's magnetic field, growth of the inner core, changes in mantle convection through time, and impact of biology.
Earth formation and evolution / D.J. Stevenson -- The composition and major reservoirs of the earth around the time of the moon-forming giant impact / A.N. Halliday, B.J. Wood -- Formation of Earth's core / D.C. Rubie, F. Nimmo, H.J. Melosh -- Magma oceans and primordial mantle differentiation / V. Solomatov -- Water, the solid earth, and the atmosphere : the genesis and effects of a wet surface on a mostly dry planet / Q. Williams -- Plate tectonics through time / N.H. Sleep -- Mechanisms of continental crust growth / M. Stein, Z. Ben-Avraham -- Thermal evolution of the mantle / G.F. Davies -- Thermal and compositional evolution of the core / F. Nimmo -- History of earth rotation / W.R. Peltier -- Coevolution of life and earth / G.J. Retallack.
Record to be deleted
Includes bibliographical references.
Keywords: Historical geology; Geophysics; Earth -- Origin